Is There a Link Between Cognitive Reserve and Cognitive Function in the Oldest-Old?. (22nd July 2017) - Lavrencic, Louise M; Richardson, Connor; Harrison, Stephanie L; Muniz-Terrera, Graciela; Keage, Hannah A D; Brittain, Katie; Kirkwood, Thomas B L; Jagger, Carol; Robinson, Louise; Stephan, Blossom C M
Abstract: Background: The oldest-old (aged ≥85 years) are the fastest growing age group, with the highest risk of cognitive impairment and dementia. This study investigated whether cognitive reserve applies to the oldest-old. This has implications for cognitive interventions in this age group. Methods: Baseline and 5-year follow-up data from the Newcastle 85+ Study were used ( N = 845, mean age = 85.5, 38% male). A Cognitive Reserve Index (CRI) was created, including: education, social class, marital status, engagement in mental activities, social participation, and physical activity. Global (Mini-Mental State Examination) and domain specific (Cognitive Drug Research Battery subtests assessing memory, attention, and speed) cognitive functions were assessed. Dementia diagnosis was determined by health records. Logistic regression analysis examined the association between CRI scores and incident dementia. Mixed effects models investigated baseline and longitudinal associations between the CRI scores and cognitive function. Analyses controlled for sex, age, depression, and cardiovascular disease history. Results: Higher reserve associated with better cognitive performance on all baseline measures, but not 5-year rate of change. The CRI associated with prevalent, but not incident dementia. Conclusions: In the oldest-old, higher reserve associated with better baseline global and domain-specific cognitive function and reduced risk of prevalent dementia; but not cognitive decline or incident dementia. Increasing reserve could promote cognitive function in the oldest-old. The results suggest there would be little impact on trajectories, but replication is needed. Development of preventative strategies would benefit from identifying the role of each factor in building reserve and why rate of change is not affected.